Implementasi Pengaturan Arak Bali Dalam Peraturan Gubernur Bali Nomor 1 Tahun 2020 Tentang Tata Kelola Minuman Fermentasi dan/atau Destilasi Khas Bali - I Wayan Arya Sugiarta; Sri Sulandari; I Nyoman Suargita (Public Inspiration : Jurnal Administrasi Publik, 2022)
Arak Bali, became a local commodity of Balinese society that has existed for generations. Balinese wine is produced traditionally, distributed locally independently by traditional arak craftsmen. With the affordable price, Balinese wine can be consumed by various groups including children who are still underage. Consumption of Balinese wine is an integral part of Balinese culture, especially in religious ceremonies. The existence of Balinese wine is not only for consumption but has a special role as a means of "tetabuhan" ceremony. This is a special concern of the Governor of Bali Wayan Koster, where the governor of Bali is trying to raise the degree of Balinese arak so that it can compete with other alcoholic beverages that have a high selling value, and it is even possible to become an export commodity as a drink with the character of Balinese khan. In Bali Governor Regulation Number 1 of 2020 concerning Management of Balinese Fermented and/or Distilled Drinks, the provincial government of Bali tries to regulate the licensing and distribution of Balinese wine. However, the government regulation is deemed ineffective due to two factors, namely: first, the regulation does not regulate criminal sanctions so that it does not provide a deterrent effect to violators of the rules which causes weak public awareness to comply with these regulations. Second, a strong Balinese culture is not easy to change and requires consistency to build Balinese public awareness to comply with Bali Governor Regulation Number 1 of 2020 concerning Governance of Balinese Fermented and/or Distilled Drinks.